Experimental and numerical investigation of formability and ductile fracture in incremental sheet forming - Gatea, Shakir Madhloom (2017)
Incremental sheet forming (ISF), also referred to as single point incremental forming (SPIF), is a relatively new, flexible forming process. The ISF process has excellent adaptability to CNC milling machines due to the fact that it does not require the use of high capacity presses or specific dies and is easy to automate for both symmetric and non-symmetric shapes. In SPIF, a blank sheet is fixed by a holder onto a CNC milling machine. A workpiece is formed by the action of a small hemispheric tool in contact with the blank moving along a user-specified tool path and incrementally deforming the blank into the desired shape. According to the technical characteristics of ISF, it can be used to manufacture small batch and customised products. SPIF is a promising technique, which could be further developed as an alternative manufacturing approach for customised medical parts, e.g. cranial plates, with considerable benefits in lead time and cost reduction. This thesis reports the findings of finite element (FE) analyses and experimental investigations into the formability and fracture in the ISF process, and their application with regard to manufacturing cranial plates, as well as the applicability of using the ISF process to form aluminium matrix composite (AMC). A modified Gurson–Tvergaard-Needleman (GTN) damage constitutive model was developed with the consideration of shear. The developed GTN model was implemented in Abaqus/Explicit via a VUMAT user subroutine to predict ductile fracture in the ISF process due to void nucleation, growth and coalescence. In comparison with experimental testing, there is a good agreement in the occurrence of fracture. The results also show that shear plays a role under meridional tensile stress in accelerating fracture propagation in ISF processes. The Nakajima test was used to construct the forming limit curve at necking (FLCN) and fracture (FLCF) for pure titanium sheet. The results of the FLCF are compared with those of the ISF to evaluate the ability of the Nakajima test to describe the fracture in ISF. Due to the fact that the GTN model can be used to capture fracture occurrence at high stress triaxiality, and the shear modified GTN model was developed to predict the fracture at zero stress or even negative stress triaxiality, the original GTN model and shear modified GTN model may not be suitable to predict the fracture in all samples of the Nakajima test, as some samples are deformed under moderate stress triaxiality. Therefore, another GTN based model with the consideration of stress triaxiality was developed to predict fracture in the Nakajima specimens under different stress triaxiality. The experimental and FE results showed that the shear modified GTN model predicted the fracture accurately with samples under uniaxial tension conditions due to low stress triaxiality and the original GTN model was suitable for an equi-biaxial strain state (high stress triaxiality). On the other hand, the stress triaxiality modified GTN model should be used for samples which have moderate stress triaxiality. The Nakajima test can be applied to establish the FLCF, which in turn can be utilized to describe the formability of the SPIF test for conical and pyramidal truncated specimens. Experiments and FE analyses were conducted to evaluate the influence of major forming parameters, including the step size, feed rate and tool size, on the formability and fracture of pure titanium. Two types of pure Ti (grades 1 and 2) were used to evaluate the sensitivity of the material type to forming parameters. It was found that the ISF parameters have different degrees of effect on the formability and fracture occurrence of pure titanium, and that grade 2 pure Ti is more sensitive to forming parameters. The optimal parameters from the parametric study were used to investigate the feasibility of using ISF to form a cranial plate; the results show that ISF can satisfactorily form a cranial plate. By evaluating the deformation and fracture mechanisms of a 6092Al alloy metal matrix composite reinforced with 17.5p vol. % SiC particles (6092Al/SiCp), the applicability of the ISF process to form the 6092Al/SiCp aluminium matrix composite (AMC) was investigated. Tensile tests were carried out at different strain rates to study the microstructure and topography of the 6092Al/SiCp sheet by scanning electron microscopy (SEM), coupled with energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The results show that this AMC material at T6 condition is brittle due to the formation of precipitations as a result of either the interaction between the Al and SiCp or from hardening precipitation treatment e.g. Al2Cu, Al4Cu2Mg8Si7 and MgAl2. O-condition annealing was therefore used to reduce the detrimental effect of the intermetallic compounds in the interface region and can improve the fracture toughness and ductility of the material. However, the Al/SiC sheet treated with O-condition annealing is more sensitive to the strain rate than that treated with T6. By investigating the feasibility of using SPIF to form AMC sheets for the first time, the results show that the 6092Al/SiCp sheets can be satisfactorily formed after O-condition annealing.